PENGEMBANGAN PARAGRAF DAN KUALITASNYA PADA KARYA TULIS ILMIAH MAHASISWA MAGISTER TEKNOLOGI PENDIDIKAN PROGRAM PASCASARJANA UNIVERSITAS JAMBI - Budiyono, Herman (Program Magister Teknologi Pendidikan Universitas Jambi, 2012)
Purpose of this research is description of the expansion pattern and quality at masterpiece writes scientific of student Master of Education Technology,Program Post Master, University of Jambi. Research method applied is quantitative descriptive. Population of research is all masterpieces writes, the numbers 25 articles. From every masterpiece writes is scientific is taken two paragraphs contents of at random as the sample, gotten 50 content paragraphs. Research data is analysed quantitatively, the step: seeking is frequency distribution by paragraph according to the expansion pattern, distribution based on quality of paragraph expansion, and percentage every expansion pattern of paragraph based on the quality. Result of research shows there are seven paragraph expansion pattern types, that is comparison and contradiction, example, process, because to effect, general to special, special to general, and definition of wide. Quality of type firstly (good: 6% and good enough: 8%), second (good:4%, good enough: 2%, and unfavourable: 2%); third (good enough: 2%); fourth (good enough: 4% and unfavourable: 2%); fifth (good: 10%, good enough: 14%, and unfavourable: 8%); sixth (good: 8% and good enough: 4%); and seventh (good: 14%, good enough: 10%, and unfavourable: 2%). Based on result of research is suggested that student to comprehend expansion patterns of paragraph that is at the same time is way of thinking, causing can communicate with pattern variatif and effective; policy taker of communications area can exploit result of this research as component of the consideration; and continuation researcher can exploit this to extend research knowledge writes. Keywords : the expansion, paragraph, quality, work science